Factors associated with TB screening among agricultural workers in Limpopo Province, South Africa - Nosimilo Mlangeni; Molebogeng Malotle; Felix Made; Jonathan Ramodike; Yandisa Sikweyiya; Christine Du Preez; Nikki Stuart Thompson; Muzimkhulu Zungu (Taylor & Francis Group, 2023)
Background Tuberculosis (TB) continues to be a public health issue of concern in South Africa. Workers in the agricultural sector are generally at increased risk of TB due to multiple interacting factors such as exposure to silica dust, co-worker infection, and occupations falling within the lower socio-economic sectors. Objective This study investigates factors associated with TB screening uptake for agricultural workers in Limpopo Province, South Africa. Method This cross-sectional study targeted a study population of 16,787 agricultural workers across 96 agricultural worksites in South Africa. A two-stage cluster random sampling design identified 24 agricultural worksites and a potential 2500 participants. The outcome variable was self-reported TB screening. Descriptive statistics and unadjusted and adjusted logistic regression analyses were performed to determine factors associated with TB screening. A literature review informed the selection of covariates as possible confounders. Results The final study sample comprised 2144 workers across 24 sites, with 55% being women. TB screening uptake was 1155 (56.3%). Factors such as living with human immunodeficiency virus (HIV) (AOR 3.16, 95% CI: 2.44-4.09), accessing health services in the workplace (AOR 1.94, 95% CI: 1.09-3.46), and having prior TB knowledge (AOR 18.45, 95% CI: 9.8-34.74) were positively associated with TB screening. Participants in the age group 36-49 years had significantly higher odds of self-reporting TB screening, compared with those aged 18-25 years (AOR 1.37, 95% CI 1.07-1.77). Migrant workers from Mozambique (OR 0.52, 95% CI: 0.34-0.79) and Zimbabwe (OR 0.71, 95% CI 0.57-0.89) were significantly less likely to self-report TB screening compared to their South African counterparts. Conclusion The findings underscore the importance of workplace health services in achieving end-TB targets. We recommend programs and interventions for preventing TB in South Africa that target the agricultural sector in general, and in particular migrant workers.